Percutaneous radiofrequency ablation for small hepatocellular carcinoma in hepatic dome under MR-guidance: clinical safety and efficacy. (1st January 2020) - Chen, Jin; Lin, Zhengyu; Lin, Qingfeng; Lin, Ruixiang; Yan, Yuan; Chen, Jian
Abstract: Purpose: To evaluate the clinical safety and efficacy of percutaneous radiofrequency ablation (RFA) using multitined expandable electrodes under magnetic resonance imaging (MRI) guidance in the treatment of small hepatocellular carcinomas (HCCs) in the hepatic dome. Materials and methods: The data of 49 patients with 50 HCC lesions in the hepatic dome who underwent MRI-guided RFA from April 2010 to January 2018 were retrospectively analyzed. Planning, targeting, and controlling were performed under MR-guidance during the procedure. The complications after RFA were observed. Follow-up MRI was performed to evaluate the curative effect. The local progression-free survival, recurrence-free survival, and overall survival rates were calculated using the Kaplan-Meier survival curve. Results: The procedures were successfully accomplished in all patients without major complications. The mean follow-up time was 36.9 ± 25.8 months (range, 3–99 months). Technical success was 100% after one RFA session with MRI assessment after 1 month. Local tumor progression was observed in one patient (2%) with the lesion located in the hepatic dome at 4 months on a subsequent follow-up MRI. The progression-free survival time was 25.0 ± 22.7 months (median, 17.0 months). The 1-, 3-, and 5-year local tumor progression-free survival rates were all 98.0%. The 1-, 3-, and 5-year recurrence-free survival rates were 68.1%, 39.9%, and 28.5%, respectively, and the estimated overall survival rates were 93.7%, 76.3%, and 54.3%, respectively. Conclusion: Planning, targeting, and controlling of RFA were well supported by MRI with acceptable time. MRI-guided RFA for small HCCs in the hepatic dome is safe and effective with fewer RF sessions.